Social Determinants of Health: A Case Study of PM 2.5 Microns Affecting on Health Status of People Living in Bangkok - Boonlert, Mitta; Mahaarcha, Wanippol (Suan Dusit Graduate School Academic Journal, 2024)
The PM 2.5 situation, people in Bangkok were affected by their lifestyles. People living in the area may be affected differently as a result of individual health factors as well as various inequality factors in society. This study aimed to investigate the impact of PM 2.5 on physical and mental well-being in Bangkok and explore the social determinants contributing to these health outcomes. A quantitative research methodology was employed by using questionnaires to collect data from 400 respondents in areas where PM 2.5 concentration exceeded the threshold and sampling by randomly selecting of house numbers in the area. The data analysis was implemented through descriptive statistics and multiple regression analysis. The findings revealed that a significant portion of participants experienced low physical well-being impacts when exposed to PM 2.5, with symptoms including a sore throat, a burning nose, and ocular discomfort. The participants also exhibited lower mental health scores compared to the broader population. The study also examined the correlation between personal factors and triggering factors, including gender, monthly income, housing type, exposure duration to PM 2.5 (3-8 hours), psychological well-being, and self-protective measures against PM 2.5. Mental health variables included age, study duration, career choices and exposure duration to PM 2.5 (1-6 hours per day). The study suggested that agencies responsible for addressing PM 2.5 should consider social factors, particularly inequality among affected areas. The importance of safeguarding oneself against PM 2.5's effects was emphasized, and the establishment of mental health facilities was recommended.